Integrated Nutrient Management Practices for Glori lily (Gloriosa superba L.) (Open Access Journal of Medicinal and Aromatic Plants, 2011)
Field experiments were conducted at the farmers’ field, Devanur village, Ariyalur District, Tamilnadu during 2007-2009 to study the effect of Integrated Nutrient Management (INM) practices on the yield performance of Glory lily (Gloriosa superba L.). The experiment was conducted in split-plot design with three replications. The treatments consisted of different organic manures in main plots (M2- farmyard manure (FYM) at 12.5 t ha-1, M3-enriched farmyard manure (EFYM) at 750 kg ha-1 and M4- pressmud compost at 5t ha-1 along with M1-control) and different levels of inorganic nitrogen in sub-plots (S1-100% N, S2-75% N, S3-50% N and S4-25% N along with S0-control). Among the organic manures, application of EFYM at 750 kg ha-1 recorded the highest yield attributes like number of capsules plant-1, number of seeds capsule-1, test weight (g), seed yield and tuber yield. Among the levels of inorganic nutrients , nitrogen application of 100 % recommended N (120 kg ha-1) recorded the highest yield attributes, seed yield and tuber yield. With regard to interaction effect, integrated use of EFYM at750 kg ha-1 and 75% inorganic nitrogen registered the highest values of yield attributes, seed yield and tuber yield.